Ежекторний детонаційний двигун на екологічно чистих компонентах палива - Сосновська, Олександра Валеріївна; Золотько, Олександр Євгенович; Золотько, Олена Василівна; Столярчук, Віталій Васильович (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2021)
The subject of research in the article is engines operating on the detonation principle of converting the energy of the working fluid. In recent years, there has been an exponential growth in the number of scientific papers devoted to detonation engines, and the most promising direction is the study of detonation engines with an ejector nozzle (EN). The work aims to obtain the results of studies of the defining characteristics of a detonation engine with an ejector nozzle. The main tasks are the scientific analysis of the working process of the pulse detonation engine with EN; modeling of working processes occurring in the flow path of the engine; numerical implementation of a mathematical model and a computational experiment. Methods, for the numerical implementation of the model of a detonation engine with an ejector, a finite-difference TVD scheme of the second order of accuracy was used. According to the results of the work performed, we observe two regions on the pressure curves, within which the pressure remains unchanged for a certain time interval (pressure plateau). An increase in the length of the ejector leads to an increase in the duration of the stage of the outflow of detonation products from the flow path of the engine, an increase in the added mass of atmospheric air, and contributes to a significant increase in the specific impulse of thrust. The value of the thrust impulse was obtained by integrating the excess pressure on the traction wall over time. Conclusions. The scientific novelty is as follows. The change in pressure overtime on the traction wall of the detonation chamber when using cylindrical EHs of different lengths was investigated by the method of numerical simulation. The value of the thrust coefficient of the ejector nozzle for the starting conditions is obtained. The studies carried out in this work are aimed at analyzing the operating mode of a promising propulsion system and are aimed at modeling the gas-dynamic processes of a pulsed detonation engine with an ejector to obtain the data necessary for preliminary design, consideration of alternative design options, and an operational assessment of the possible characteristics of an engine with an ejector. The main advantages of the engine are the ultra-high-speed of energy release in the detonation process, which leads to an increase in the efficiency of the thermodynamic cycle, simplification and cost reduction of the design, and a significant gain in in-flight performance.